2011
DOI: 10.1007/s00412-011-0328-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and nuclear architecture of immune cells after LPS activation

Abstract: Changes in the nuclear positioning of specific genes, depending on their expression status, have been observed in a large diversity of physiological processes. However, gene position is poorly documented for immune cells which have been subjected to activation following bacterial infection. Using a pig model, we focused our study on monocyte-derived macrophages and neutrophils, as they are the first lines of defence against pathogens. We examined whether changes in gene expression due to LPS activation imply t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 79 publications
1
19
0
Order By: Relevance
“…In experiment GSE7314, IGF2 was over-expressed in pigs inoculated with Salmonella choleraesuis at 21 dpi relative to non-inoculated pigs ( P -value < 8.1 × 10 -4 ). These results are consistent with reports that IGF2 is down-regulated in pigs immune-challenged with lipopolysaccharide [44]. …”
Section: Resultssupporting
confidence: 94%
“…In experiment GSE7314, IGF2 was over-expressed in pigs inoculated with Salmonella choleraesuis at 21 dpi relative to non-inoculated pigs ( P -value < 8.1 × 10 -4 ). These results are consistent with reports that IGF2 is down-regulated in pigs immune-challenged with lipopolysaccharide [44]. …”
Section: Resultssupporting
confidence: 94%
“…This non-random organization probably relies on functional constrains to regulate genome activity, ie regulation of gene expression. Thus, the nuclear environment could favors gene specific interactions between distant genomic regions to activate or repress their transcriptional activities [5], [6] but also modulate genes position within their respective chromosome territories, depending on their expression status [7][10]. However to date little is known on how this three-dimensional organization is controlled and transmitted through cell division but also through generations.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that transcriptional activation of genes by hormone addition was not connected with changes in the nuclear gene positioning [Kocanova et al, 2010;Hakim et al, 2011]. Similarly, variations in expression levels that occurred during bacterial infection did not induce global repositioning of genes in the nuclear space of porcine macrophages [Solinhac et al, 2011]. Studies concerning the parasite influencing the host interphase genome organization have revealed gene repositioning events, but the behavior of the up-regulated genes was different -one of the studied genes moved to the nuclear interior and the other one moved to the nuclear edge [Knight et al, 2011].…”
Section: Resultsmentioning
confidence: 98%
“…Depending on the type of detected objects (genes or chromosome territories) the global thresholds are computed differently. If necessary, the segmentation thresholds were adjusted manually to improve object detection [Iannuccelli et al, 2010;Solinhac et al, 2011]. To determine the radial position of studied genes the ratio of measurement distance was calculated ( R = distance from the FISH signal to the nucleus center by distance from the FISH signal to the nuclear border).…”
Section: Microscopy and Image Analysismentioning
confidence: 99%